2021
DOI: 10.1007/s10029-021-02378-9
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization criteria of patients on scheduled waiting lists for abdominal wall hernia surgery: a cross-sectional study

Abstract: Purpose Long delays in waiting lists have a negative impact on the principles of equity and providing timely access to care. This study aimed to assess waiting lists for abdominal wall hernia repair (incisional ventral vs. inguinal hernia) to define explicit prioritization criteria. Methods A cross-sectional single-center study was designed. Patients in the waiting list for incisional/ventral hernia ( n = 42) and inguinal hernia ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…To our knowledge, this is the first emergency groin hernia repair study to report postoperative morbidity using this risk scale. According to these findings, elderly patients with associated comorbidities, and especially women, could benefit from elective inguinal hernia repair to avoid the risks of emergency intervention for inguinal hernia, as reported in previous studies [4,30].…”
Section: Discussionsupporting
confidence: 69%
“…To our knowledge, this is the first emergency groin hernia repair study to report postoperative morbidity using this risk scale. According to these findings, elderly patients with associated comorbidities, and especially women, could benefit from elective inguinal hernia repair to avoid the risks of emergency intervention for inguinal hernia, as reported in previous studies [4,30].…”
Section: Discussionsupporting
confidence: 69%
“…On the other hand, a steady curve before and during the pandemic regarding the number of urgent hernioplasty has been also reported 9 . Lastly, some authors suggested that in mildly symptomatic patients a safe management of the waiting list was obtained through the assessment of analgesic consumption and anamnestic frailty 10 …”
Section: Discussionmentioning
confidence: 99%
“…9 Lastly, some authors suggested that in mildly symptomatic patients a safe management of the waiting list was obtained through the assessment of analgesic consumption and anamnestic frailty. 10 During the pandemic time, it was debated the feasibility of the Taxis maneuver in order to procrastinate as much as possible on the hernia correction presented in an emergency setting, in most cases at the expense of a worsened quality of life perception and patient safety. Some authors suggested that a successful Taxis maneuver can safely postposed surgery for weeks, 11 but others argued that it has been shown the impossibility of recommending the Taxis maneuver as the main part of an algorithm for the evaluation and treatment of patients with the onset of painful groin hernia, due to the lack of evidence in the current literature.…”
Section: Discussionmentioning
confidence: 99%
“…The development of the online platform ensured that surgeons could use it to guide their practices for dealing with ventral hernias ( 19 ). In another study, López-Cano et al argued that the incorporation of artificial intelligence techniques could improve the delivery of patient care by combining and analyzing thousands of abdominal hernia cases and classifying them based on severity and prioritization ( 20 ). Artificial intelligence in abdominal hernia surgery is evident via the research conducted by Elhage et al, which aimed to apply three deep learning models to predict complexity and wound infections after an abdominal hernia procedure ( 21 ).…”
Section: Discussionmentioning
confidence: 99%